1985
DOI: 10.1037/h0085522
|View full text |Cite
|
Sign up to set email alerts
|

Adapting psychotherapy for the depressed, unacculturated, acting-out, Black male adolescent.

Abstract: The psychopathology of poor, unacculturated, black male adolescents is underdiagnosed, undertreated, and misunderstood. Their differences distract from the basic conditions that they share with other adolescents. Depression in adolescence accompanied by destructive acting-out behavior is explored with special reference to the poor, black male's experience. Clinically based suggestions are given for the successful therapeutic management of these youths.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

1990
1990
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“…The current study attempts to address the problem of low levels of therapy engagement and participation among African American youth by examining whether and how therapist behavior and content focus within the therapy session influences adolescent engagement into the treatment process. This study was informed by culturally responsive treatment models (e.g., Malgady, Rogler, & Costantino, 1990;Paster, 1985), knowledge of risk and protective factors of substance abuse and conduct disorder (Belgrave et al, 1994;Hawkins, Catalano, & Miller, 1992;Kandel, Kessler, & Margulies, 1978;Newcomb & Bentler, 1989;Newcomb & Felix-Ortiz, 1992;Palmer & Liddle, 1995), and most important, by scholarly works advocating the use of African American culture in the design of behavioral treatments for African American adolescents (Boyd-Franklin, 1989;Brookins, 1996;Paster, 1985;Rowe & Grills, 1993;Vontress, 1995). Whereas there are no empirical studies linking discussion of particular therapy content to adolescent engagement behaviors in therapy sessions, a review of empirical, theoretical, historical, and media sources relating to African American youth and families yielded themes thought to be salient to the culture of Black male substance-abusing adolescents targeted in this study.…”
mentioning
confidence: 99%
“…The current study attempts to address the problem of low levels of therapy engagement and participation among African American youth by examining whether and how therapist behavior and content focus within the therapy session influences adolescent engagement into the treatment process. This study was informed by culturally responsive treatment models (e.g., Malgady, Rogler, & Costantino, 1990;Paster, 1985), knowledge of risk and protective factors of substance abuse and conduct disorder (Belgrave et al, 1994;Hawkins, Catalano, & Miller, 1992;Kandel, Kessler, & Margulies, 1978;Newcomb & Bentler, 1989;Newcomb & Felix-Ortiz, 1992;Palmer & Liddle, 1995), and most important, by scholarly works advocating the use of African American culture in the design of behavioral treatments for African American adolescents (Boyd-Franklin, 1989;Brookins, 1996;Paster, 1985;Rowe & Grills, 1993;Vontress, 1995). Whereas there are no empirical studies linking discussion of particular therapy content to adolescent engagement behaviors in therapy sessions, a review of empirical, theoretical, historical, and media sources relating to African American youth and families yielded themes thought to be salient to the culture of Black male substance-abusing adolescents targeted in this study.…”
mentioning
confidence: 99%
“…In contrast, Lothstein (1985) and Paster (1985) contended that psychoanalytically oriented psychotherapy is appropriate for use with African American male adolescents. Paster stated that these men are responsive to treatment if their problems are understood and if their needs are appropriately met.…”
Section: Specific Therapeutic Techniques and Theoretical Frameworkmentioning
confidence: 86%
“…Several authors have specifically addressed problems associated with combining data from African American male and African American female clients when examining psychopathology in clinical research. Myers and King (1983) and Paster (1985) suggested that the greater likelihood for African American men to drop out of school, to use chemical substances, and to be incarcerated, renders them more likely than African American women to experience psychological disturbances.…”
Section: Psychotherapy and African American Menmentioning
confidence: 97%
“…In addition, they often receive more externalizing diagnoses (Minsky et al, 2006; Nguyen, Huang, Arganza, & Liao, 2007) which generally result in more restrictive and correctional placements. Histories of interacting with authority figures who are “accepting, non-manipulative, non-punitive, and yet strong” within various settings may be severely lacking (Paster, 1985, p. 413). Hence, many Black males are likely to simply view counselors as institutional agents that are there to do the biddings of the systems in which they work rather than as an ally or source of help.…”
Section: Discussionmentioning
confidence: 99%